Obesity as a Neurobiologic Disorder: A Heavyweight Contender - Chávez-Castillo, Mervin; Duran, Pablo; Garrido, Bermary; Díaz, Andrea; Escalona, Daniel; Cano, Clímaco (Current Psychiatry Research and Reviews, 2023)
Obesity is a multifactorial metabolic condition characterized by an abnormal or excessive accumulation of fat in the adipose tissue, capable of decreasing life expectancy. Chronically, the exacerbated inflammatory response interferes with the proper functioning of organs and tissues, becoming the cornerstone of various major metabolic imbalances in different systems, such as the central nervous system. Considering this, obesity’s meta-inflammation indirectly affects brain regions related to psychiatric illnesses and cognitive function. Also, it has been established that several neurobiological mechanisms related to appetite regulation and impulse control disorders could explain the onset of obesity. Thus, due to the high prevalence of mental illnesses linked to obese patients and the fact that a bidirectional relation between these two entities has been observed, many efforts have been made to establish an effective and secure pharmacological approach to obesity. In this context, several psychotropics and appetite- suppressant drugs, along with lifestyle changes, have been highlighted as promising therapeutic tools against obesity.
Keywords: Obesity